Analysis of Blood Group Discrepancy at Dr. Wahidin Sudirohusodo Hospital's Blood Transfusion Unit Makassar - Erdayanti Erdayanti; Rachmawati Muhiddin; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Discrepancy is a lack of compatibility of blood group tests between forward grouping and reverse grouping. Based on the cause, discrepancies are divided into four groups as follows: group I discrepancies, which occur due to weak or missing antibodies, group II discrepancies, which occur due to weak or missing antigens, group III discrepancies, which result in the formation of rouleaux, and group IV discrepancies, which are caused by other problems. A retrospective study was carried out by using ABO blood group data, which were analyzed by the automatic gel test method with the IH-1000 device. Data from January 2019 to December 2021 was collected at the Blood Transfusion Unit, Dr. Wahidin Sudirohusodo Hospital of Makassar, and the data were grouped using SPSS version 22. A total of 21.742 samples were tested. The number of detected ABO blood group discrepancies was 127 (0.58%). There were 68 (51.3%) males and 59 (46.5%) females with an age range divided into toddler (38.6%), child (2.4%), adolescent (13.4%), adult (8.7%), pre-elderly (17.3%), and elderly (6.3 %). Based on the disease, discrepancies were categorized into samples with infectious disease (33.9%), autoimmune disease (3.9%), malignancy (23.6%), chronic disease (11%), and others (27.6%). The discrepancies consisted of group I (70.9%), group II (0%), group III (0.8%), and group IV (28.3%). There was a significant correlation between age and blood group discrepancy with p < 0.001 and moderate correlation strength (0.54). The prevalence of discrepancy in this study was 0.58%. Discrepancies must be resolved before they are reported to minimize transfusion reactions.